Hubungan Pengetahuan Dan Sikap Remaja Dalam Mengkonsumsi Tablet Zat Besi Di Sma Swasta Tunas Bangsa Kwala Begumit Kecamatan Binjai Kabupaten Langkakat Tahun 2022 - Desliza Desliza; Eka Purnama; Srilina Br Pinem; Ninsah Mandala Putri; Henny Rista (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Adolescence is a transition period from childhood to adulthood which requires higher levels of nutrients, including iron. Teenage girls are more susceptible to anemia because they are already menstruating (Sediaoetama, 2018). Lack of iron in adolescents without adequate iron intake will continue during pregnancy, causing suboptimal fetal growth, low birth weight, risk of bleeding during delivery and increasing the risk of maternal and infant mortality. That's why most Obstetricians and Nutrition experts recommend iron supplements from pre-conception (adolescence). The aim is to determine the relationship between knowledge and attitudes of teenagers in consuming iron tablets at Tunas Bangsa Kwala Begumit Private High School, Binjai District, Langkat Regency in 2022. This type of research is analytical research with a cross sectional design, namely the researcher takes samples from a population using a questionnaire as a data collection tool to determine the relationship between knowledge and attitudes of teenagers in consuming iron tablets at Tunas Bangsa Kwala Begumit Private High School, Binjai District, Langkat Regency. 2022 (Hermanto, 2015). Conclusion: From a total of 39 young female respondents, the results showed that the majority of respondents had poor knowledge, 18 respondents (46.2%) and the minority of respondents with good knowledge, 10 people with (25.6%). Of the 39 respondents, the majority of respondents did not consume iron tablets, 29 people (74.4%). From the statistical test results, it was found that p value = 0.000 (p <0.05). This means that there is a significant relationship between knowledge and attitudes of teenagers in consuming iron tablets.